SYNDROME OF LIMITED JOINT MOBILITY IN DIABETES MELLITUS - Safinaz Ataoğlu (Archives of Rheumatology, 2002)
Typical musculoskeletal complications of diabetes mellitus include syndrome of limited joint mobility, diabetic sclerodactyly, neuropathic joints, osteolysis, carpal tunnel syndrome, DupuytrenÕs contracture, flexor tenosynovitis, adhesive capsulitis, and shoulder-hand syndrome. Of these, only limited joint mobility syndrome, and diabetic sclerodactyly occur exclusively in patints with diabetes. Syndrome of limited joint mobility in diabetic patients is generally painless and seldom treated until hand deformity is severe enough to interfere with daily life. The complaints of stiffness, decreased grip strength, and loss of motion in a diabetic patient should suggest the onset of this disorder.